Green Business Innovation: Sustainable Business Model Development through Integration of Business Model Canvas, Design Thinking, and Islamic Business Ethics - Asmaraningtyas, Lussy Widia; Rahmawati, Imelda Dian; Fitriyah, Hadiah (Manunggal Halim Jaya, 2024)
This research aims to analyze the integration of Business Model Canvas (BMC), Design Thinking, and Islamic Business Ethics in the development of sustainable green business models. Through a qualitative approach using Computer-Assisted Qualitative Data Analysis Software (CAQDAS) and secondary data, this research highlights the potential of integrating these three concepts in creating a business model that is not only competitive but also ecologically, socially, and economically sustainable. The results show that BMC integration provides a structural foundation, Design Thinking facilitates creative innovation in the context of sustainability, and Islamic Business Ethics provides a strong moral framework to support the implementation and sustainability of such business models. Thus, this research provides an innovative contribution to fill the existing knowledge gap and blaze new trails in designing green business models that integrate sustainability and Islamic business ethics values.